Asymmetric Auctions with Resale - Hafalir, Isa; Krishna, Vijay (American Economic Review, 2008)
We study first- and second-price auctions with resale in a model with independent private values. With asymmetric bidders, the resulting inefficiencies create a motive for post-auction trade which, in our model, takes place via monopoly pricing—the winner makes a take-it-or-leave-it offer to the loser. We show (a) a first-price auction with resale has a unique monotonic equilibrium; and (b) with resale, the expected revenue from a first-price auction exceeds that from a second-price auction. The inclusion of resale possibilities thus permits a general revenue ranking of the two auctions that is not available when these are excluded. (JEL D44)